(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the previous decade, plastics have achieved tremendous advances in horticulture. Because of its structural integrity, chemical properties, and versatility, plastic has become a prominent material in our everyday lives. Drip irrigation, plastic mulches, packaging and storage for better product quality, and post-harvest management are just a few of the numerous uses for plastic in high-tech horticulture. The use of polymers in agriculture, horticulture, water management, food grain storage, and other industries is known as plasticulture. Despite the fact that the number of agricultural plastic manufacturers has decreased by 40% in the past 10 years, the use of plastic in horticultural crop production has risen significantly. The use of plasticulture in the cultivation of horticultural crops like veggies, tiny fruits, flowers, plantation crops, and ornamentals helps to minimize the sometimes severe weather changes that occur in various parts of the nation, particularly temperature, rainfall, and wind.